2014
DOI: 10.1039/c4ay00703d
|View full text |Cite
|
Sign up to set email alerts
|

Application of Fourier transform near-infrared spectroscopy to the quantification and monitoring of carbonyl value in frying oils

Abstract: FT-NIR method towards carbonyl value (CV) has been developed and applied in monitoring CV changes in frying process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Another quantitative calibration technique is the chemometric method, which is capable of providing precision, accuracy, and analytical information and has been widely used in recent years. One or more parameters (Talpur et al, 2014), such as peroxide value (Yu, Voort, & Sedman, 2007), total polar compounds (Ng, Wehling, & Cuppett, 2011), iodine value (Hendl, Howell, Lowery, & Jones, 2001), free fatty acid, conjugated diene and triene (Innawong, Mallikarjunan, Irudayaraj, & Marcy, 2004), and carbonyl value (Wang, Yu, Chen, Yang, & Zhang, 2014), could be determined by establishing the relationship between the chemical parameters and spectral data of oils, using chemometric methods involving partial least squares (PLS), multiple linear regression (MLR), and principal component regression (PCR) analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Another quantitative calibration technique is the chemometric method, which is capable of providing precision, accuracy, and analytical information and has been widely used in recent years. One or more parameters (Talpur et al, 2014), such as peroxide value (Yu, Voort, & Sedman, 2007), total polar compounds (Ng, Wehling, & Cuppett, 2011), iodine value (Hendl, Howell, Lowery, & Jones, 2001), free fatty acid, conjugated diene and triene (Innawong, Mallikarjunan, Irudayaraj, & Marcy, 2004), and carbonyl value (Wang, Yu, Chen, Yang, & Zhang, 2014), could be determined by establishing the relationship between the chemical parameters and spectral data of oils, using chemometric methods involving partial least squares (PLS), multiple linear regression (MLR), and principal component regression (PCR) analyses.…”
Section: Introductionmentioning
confidence: 99%
“…It is capable of measuring a number of chemical parameters including TPM, PTG, FFA, peroxides, anisidine value, and carbonyl value91617181920. Other techniques attempted for frying oil quality assessment include image processing21, E-nose2223, pore-based wicking sensor2425, HPTLC-densitometry26, and ultrasonic technique2728.…”
mentioning
confidence: 99%
“…AV was highly correlated ( p ≤ 0.05) with DC in all packaged fried foods, and the result was consistent with a previous report (Bou et al ., ). CV in the fried food was also measured, which provided valuable information regarding secondary oxidations such as aldehydes and ketones and is not easily decomposed of fried foods during storage (Wang et al ., ). A previous investigation on a set of frying oils showed that if CV is less than 43.5 mmol/kg, the oil is considered as safe and acceptable (Farhoosh & Moosavi, ).…”
Section: Resultsmentioning
confidence: 97%
“…Various parameters had been used to measure physicochemical changes of fried foods during storage such as moisture content (MC), hardness (HN), acid value (AV) (Liu et al, 2018), peroxide value (PV) (Barden & Decker, 2016), carbonyl value (CV) (Wang et al, 2014), dielectric constant (DC) (Valantina et al, 2017), fatty acid composition (FAC) and Acrylamide (AA). Although lipid oxidation is a chemical process, it can be influenced by both chemical and physical parameters (Barden & Decker, 2016).…”
Section: Introductionmentioning
confidence: 99%